IMPLEMENTATION OF CRIMINAL SANCTIONS OF NARCOTICS ABUSE AGAINST TNI OFFICERS (Military Court Decision on Case Registration Number: 49-K/PM.I-01/AD/IV/2019) - Sitti Mawar; Nelis Sa'adah (Universitas Islam Negeri Ar-Raniry, 2021)
Narcotics abuse is a crime that violates the rule of law, which can threaten the safety of both the physical and the soul of the user. As we know, narcotics abuse is not only for civilians, but in reality, TNI personnel are also involved in narcotics abuse. The TNI is a state apparatus whose duty is to guard, protect, maintain security and safeguard the sovereignty of the State. The imposition of basic criminal sanctions for TNI personnel for narcotics abuse refers to Law Number 35 of 2009 Article 127 paragraph 1 which states that people who abuse narcotics class I for themselves are sentenced to a maximum imprisonment of 4 years. However, Article 6 of the Military Criminal Law (KUHPM) provides additional types of punishment, namely dismissal from military service, demotion and revocation of certain rights. In this thesis, the formulation of the problem is how the judge's consideration in imposing a relatively light sentence for narcotics abuse on TNI personnel (Military Court Decision Case Number 49-K/PM.I-01/AD/IV/2019) and how the author's analysis is based on ( Military Court Decision Case Number 49-K/PM.I-01/AD/IV/2019). The research method used in this thesis is normative sourced from legislation. Based on the decision of the Military Court Judge I-01 Banda Aceh that narcotics abuse against TNI personnel is punishable by 2 years in prison. In addition, additional criminal sanctions were imposed, namely dismissal from the Military Service. The basis of the judge's consideration in reducing the defendant's sanctions on the basis of the defendant's level of guilt, the defendant admits his actions openly, the defendant is the breadwinner of the family, has never been sentenced or is a recidivist, is polite in front of the trial, has regrets and promises not to repeat it. For law enforcers, especially military judges, in imposing imprisonment sanctions, they must be in accordance with the law.